Diagnostics and farmacological treatment of ocular cicatrical pemphigoid - Brydak-Godowska, Joanna; Moneta-Wielgoś, Joanna; Pauk-Domańska, Magdalena; Dróbecka-Brydak, Ewa; Samsel, Agnieszka; Kęcik, Mariusz; Kowalewski, Cezary; Mackiewicz, Wojciech; Kęcik, Dariusz (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Ocular cicatricial pemphigoid (OCP) is an autoimmune disease characterize by mucous membrane fibrosis and skin changes resulting with scarring. The pathogenic mechanisms of ocular cicatricial pemphigoid are incompletely understood. Antibasement membrane antibodies which lead to subepithelial blistering, granulation tissue and inflammatory infiltrate formation in the substantia propria are thought to be the main pathophysiological mechanisms in cicatricial pemphigoid. It has been found eosinophils and increased collagen type I and III. Human leukocyte antigen HLA-DR2, HLA-DR4 and DQw7 genotypes have been identified as conferring increased susceptibility to the development of this disease. Ocular cicatrical pemphigoid (OCP) is one of the forms of bullous pemphigoid. Initial symptoms of ocular pemfigoid are not characteristic. Conjunctival fibrosis may cause severe entropion, trichiasis, symblepharon, dry eye syndrome, corneal epithelial erosions or ulceration. Secondary glaucoma is one of the most frequent complications. Ocular cicatricial pemphigoid may be chronic, acute, or subacute disease with periodic exacerbation of conjunctival inflammation. The treatment in this disease are topical drops or ointment (lubricants, corticosteroids, antibiotics, antiglaucomatous). Oral dapsone and corticosteroids may control the activity of the disease. In other progressive cases immunosuppressive drugs must be used (azathioprine, cyclophosphamide, methotrexate, mycophenolan mofetil, daclizumab, intravenous immunoglobulin therapy). To make an early diagnosis of ocular cicatricial pemphigoid, biopsy and immunohistochemical analysis of conjunctiva should be performed in every case of persistent conjunctival inflammation.